Application of Virtual Reality Technology and 3D Technology in Game Animation Production - Zehao Wang; Ye Deng; Wenlong Chen (International Transactions on Electrical Energy Systems)
With the increasing pressure of modern young people, they begin to look for various ways to relax. Among them, game animation makes them immersive and has a low experience cost, which is one of the best ways to relax. Therefore, animation games have been welcomed by more and more young people. However, virtual reality technology and 3D technology have played a huge role in the production of game animation. Therefore, this paper aimed to study how virtual reality technology and 3D technology were applied in game animation production and put forward their advantages. This paper also proposed a method based on virtual reality technology and 3D technology and analyzed the production of game animation. The experimental results of this paper showed that in the survey results of the popularity of the A game, only 56 experiencers thought its effect was good, accounting for 18%. There were 145 experiencers who disliked the A game because they thought the A game was very boring and the game scene was very simple. In the survey results of the popularity of the B game, 222 experiencers liked this game, accounting for 71.6%, and 43 experiencers did not like the B game because they thought the 3D effect of the B game would make them dizzy and uncomfortable. It can be seen that the integration of virtual reality technology and 3D technology into game animation production is more popular, so the research in this paper is meaningful.